Learning from teachers like us: using video to move beyond 'secret knowledge' in Papua New Guinea elementary teacher professional development. Issue 1 (19th May 2021) - Simoncini, Kym; Pamphilon, Barbara; Smith, Hilary
ABSTRACT: Providing professional development (PD) for Papua New Guinea (PNG) teachers is highly challenging due to the remoteness of schools, limited budgets, travel costs, and safety. The essential follow-up guidance and support after PD workshops is rarely possible, especially for the majority of teachers, who work in rural schools. In addition, the effectiveness of PD in facilitating collaboration among members of the school community can be affected by traditional cultural approaches to knowledge building and sharing. This article reports on an innovative form of PD with PNG elementary school teachers that used classroom teaching videos provided on SD cards for mobile phones. Videos of authentic teaching by other PNG teachers in similar contexts were provided to 260 teachers as follow-up to literacy practice workshop training sessions. The SD cards were used by 80% of the teachers in their own teaching, and more than half also shared the SD cards with other teachers. These findings show the value of SD cards in PD training in low-income countries, both for the development of individual teacher self-efficacy leading to confidence and better outcomes for the children in their classes, and for the development of teacher collaboration with colleagues